'I'm competitive with myself': A study of women leaders navigating neoliberal patriarchal workplaces. Issue 3 (21st November 2022) - Mavin, Sharon; Yusupova, Marina
Abstract: This paper investigates how women leaders in the UK negotiate claims of being competitive by internalizing competition. Competition is a critical component in neoliberal contexts; yet its gendered implications are under research. Through analysis of 18 women leaders' narratives who directly characterize themselves as 'competitive with myself, ' we theorize how and why competition is directed at the self. We understand articulations of 'I'm competitive with myself as a discursive strategy, which functions in the narratives in three interconnected ways. 'Competitive with myself' versus 'competitive with others' explains how women leaders internalize competition by rejecting competition with others and distancing from the conventional notion of zero‐sum game competition. 'Competing with myself for perfection' and 'Competitive with myself as a protective shield' explain why women leaders internalize competition—to perfect the self and navigate the double standards of a gendered neoliberal workplace. We argue that 'competitive with myself' as a discursive strategy enables women leaders to openly claim competitiveness, (an undesirable performance for women) and simultaneously distance themselves from it. The study contributes understandings of competition as gendered under neoliberalism and in patriarchal men‐dominated leadership roles and workplaces. Through a nuanced discussion of women leaders' narratives, we identify both an obligation to compete and a possible flexing of gender norms in relation to competition.